1984
DOI: 10.1002/jemt.1060010203
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of glutaraldehyde‐carbohydrazide copolymerization in biological specimen stabilization for scanning electron microscopy

Abstract: Biological specimens can be prepared for scanning electron microscopy by means of copolymerizing the fixing agent glutaraldehyde with carbohydrazide prior to air drying. Such preparations are more stable in the electron microscope, show less internal cellular disruption and retain more of their native elemental composition than specimens prepared by means of dehydration and critical-point drying. Specimens observed in the scanning electron microscope can often be recovered for thin sectioning with no additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The standard techniques to avoid this are critical pointdrying (CPD) and freeze-drying (FD) (Anderson, 1951;Boyde & Wood, 1969;Echlin & Moreton, 1973). However, CPD causes thermal and pressure stresses in the tissue, takes a long time and may extract cellular components in the transitional fluid (Gunning & Crang, 1984). Freeze-drying may cause surface damage due to ice-crystal formation and is also lengthy (Boyde, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…The standard techniques to avoid this are critical pointdrying (CPD) and freeze-drying (FD) (Anderson, 1951;Boyde & Wood, 1969;Echlin & Moreton, 1973). However, CPD causes thermal and pressure stresses in the tissue, takes a long time and may extract cellular components in the transitional fluid (Gunning & Crang, 1984). Freeze-drying may cause surface damage due to ice-crystal formation and is also lengthy (Boyde, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…These cells also showed rigidity, and breakage that was probably due to fast-drying by TMS of nonpliable GCs. The standard techniques to avoid these adverse effects are CPD and FD (Anderson, 1951; Boyde & Wood, 1969; Gunning & Crang, 1984). CPD, however, has been associated with thermal and pressure stresses in the tissue (Gunning & Crang, 1984) and FD takes a long time and may cause cell membrane damage due to the ice-crystal formation (Frederik & Busing, 1981; Terracio & Schwabe, 1981; Bearer & Orci, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the quality of pollen grains during sample preparation using CPD was also described in an earlier study (Adams and Morton 1972 ). Further, it was also reported that CPD can cause thermal and pressure stresses in tissues for an extended period and may extract cellular components from the transitional fluid (Gunning and Crang 1984 ).…”
Section: Introductionmentioning
confidence: 99%